Education, Certification and Licensing in the Modern Professional Environment - Toplak Perović, Pia; Koritnik, Boštjan (Celovita pot izobraževanja: Od ideje do mreženja, 2026)
Education, lifelong learning, and systems of certification and licensing play an important role in the development of professional competencies, employability, and the quality assurance of educational processes. This paper addresses the fields of formal and non-formal education, lifelong learning, recognition of competencies, and the legal and institutional regulation of certification and licensing within the European Union and Slovenia. Particular attention is devoted to European qualification frameworks, quality assurance systems, recognition of professional qualifications, and the alignment of education with labour market needs. The paper is based on the methods of analysis and synthesis of secondary literature sources, including domestic and foreign scientific articles, European strategic documents, and Slovenian legislation. The research contributes to a better understanding of the development of modern educational systems, the importance of lifelong learning, and the role of certification, licensing, and quality assurance in the development of professional competencies and trust in the educational system.